Do Menu Variety, Service Quality, and Store Atmosphere Influence Customer Satisfaction and Revisit Intention? - Bony Fasius; Ana Fitriana; Erna Listiana; Ahmadi Ahmadi (eCo-Buss, 2025)
Coffee shops have grown to play a significant role in Indonesia's coffee-drinking culture. People used to just enjoy coffee at regular coffee shops, but these days, sipping coffee has become a more sophisticated pastime. One of the coffee businesses that is now drawing a sizable customer base is Titik Narasi Coffee. As the number of coffee lovers rises, more businesspeople are interested in starting coffee shops, which is making the sector more competitive. Effective client acquisition and retention strategies are required to handle this competition. Titik Narasi Coffee provides its customers with a range of cutting-edge services in addition to an enticing location idea. In the context of Titik Narasi Coffee, this study attempts to determine the degree to which customer pleasure acts as a mediating variable between service quality and store atmosphere and customer loyalty. A causal design method was used to test the hypotheses, and the SMART PLS statistical tool and structural equation modeling (SEM) were used to analyze the interactions between independent, dependent, and mediating factors. Questionnaires from a sample of 200 respondents were used to gather data.